Balancing work and study: Determinants of academic performance among part-time students at Universitas Muhammadiyah Kalimantan Timur - Praja Hadi Saputra; Parissa Padilla (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
This research examines the extent to which time management and work–life balance contributes to the academic performance of part-time students at Universitas Muhammadiyah Kalimantan Timur. The study is grounded in the increasing demands experienced by part-time students who must simultaneously navigate academic commitments, occupational responsibilities, and personal obligations. Using a quantitative methodological approach, this study gathered data through a structured questionnaire distributed to 110 part-time students. The relationships between the independent variables and academic performance were examined using multiple linear regression analysis. The results reveal that effective time management has a positive and statistically significant effect on academic performance. Furthermore, work–life balance is found to significantly and positively contribute to students’ academic outcomes. From a theoretical perspective, this study extends the application of Expectancy Theory within the context of Indonesian higher education by demonstrating how motivational mechanisms operate among part-time students managing multiple roles. Practically, the findings underscore the importance of institutional interventions, such as time management training and flexible academic support systems, in enhancing part-time students’ academic success.